PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN DESAIN MULTIMEDIA KELAS XI SMK NEGERI 3 SURAKARTA TAHUN PELAJARAN 2015/2016 - Alin Hoerunnisa; Taufiq Lilo A diSucipto; A.G. Tamrin (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2020)
This research aims is to to improve students interest and learning achievement on the subject of Multimedia Design Class XI SMK Negeri 3 Surakarta. This research is a classroom action research with two cycles, each cycle consisted of planning, implementation, observation, and reflection of teaching and learning activities. The subject of this reserach is the students of class XI MM-1 which numbered 31 students. Data collection technique that used were interview, quisioner, observation, and test. Analysis technique implemented through comparative analysis and descriptive qualitative. Meanwhile the validity of test data using triangulation techniques. The result of reasearch shows that on the precycle activities observation the percentage of the students interest is 10,34%, after implementation of make a match learning model in the first cycle increased by 48,28% then in the second cycle increased to 82,76%. While the result of students learning achievement also increased from the value of each cycle test. On precycle test namely the implementation of the conventional method, the average learning achievement for cognitive domain of 60,96; afective domain 65,51 and psychomotor domain 76,07. On the first cycle after the implementation of make a match learning model the average learning achievement increase on cognitive domain 72,41; afective domain 74,31 and pychomotor domain 76,20. At the second cycle increased for cognitive domain 86,34; afective domain 89,48 and pychomotor domain 86,38. Research conclusion that the implementation of make a match learning model can increase the students interest and learning achievement on the subject of Multimedia Design class XI SMK Negeri 3 Surakarta. Then, the implementation of make a match learning model which improve student interest and learning achievement is make the students become active. That can be acted by presentation activity in front of the class and give opportunity to audience (other students) for giving problem solving.